Endettement des États et crise de l’euro - Bernard Billaudot (Revue de la Régulation)
Without a right diagnosis, no chance of cure. This can be stated for the Euro crisis. The diagnosis proposed in this paper is that the key origin of this crisis is not a series of high government deficits (non financial origin), but the present mode of European government financing (financial origin based on its de-nationalization in the under construction Europe context). However, about any « social disease », a right diagnosis doesn’t determine a unique therapy. So, we have as many financial solutions to the Euro crisis as there are political options on the Europe construction. The main point of this paper is to present four « pure » options with the inducted solutions. In fine, I give my own citizen point of view which is in favour of a shift for all Euro zone contries from the Euro as a unique currency to the Euro as a common currency.